Ironing Out the Details: How Iron Orchestrates Macrophage Polarization - Xia, Yaoyao; Li, Yikun; Wu, Xiaoyan; Zhang, Qingzhuo; Chen, Siyuan; Ma, Xianyong; Yu, Miao (Frontiers in Immunology, 2021)
ABSTRACT: Iron fine-tunes innate immune responses, including macrophage inflammation. In this review, we summarize the current understanding about the iron in dictating macrophage polarization. Mechanistically, iron orchestrates macrophage polarization through several aspects, including cellular signaling, cellular metabolism, and epigenetic regulation. Therefore, iron modulates the development and progression of multiple macrophage-associated diseases, such as cancer, atherosclerosis, and liver diseases. Collectively, this review highlights the crucial role of iron for macrophage polarization, and indicates the potential application of iron supplementation as an adjuvant therapy in different inflammatory disorders relative to the balance of macrophage polarization.